1997
DOI: 10.1172/jci119204
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and prolactin receptors are expressed and functioning in human prostate.

Abstract: Prolactin is widely expressed in different tissues, and it is presumed to have both local and systemic actions. In males it is known to influence reproductive functions but the significance and mechanisms of prolactin action in male accessory reproductive tissues are poorly understood. Here we show that prolactin acts as a direct growth and differentiation factor for human prostate, as measured by changes in DNA synthesis and epithelial morphology of organ cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
151
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(165 citation statements)
references
References 70 publications
8
151
0
4
Order By: Relevance
“…40,45,57,72,78,79 Active Stat5a/b decreased both cell surface and total E-cadherin protein expression ( Figure 1A) and mRNA levels ( Figure 1B). At the same time, active Stat5a/b upregulated mesenchymal markers N-cadherin, vimentin, and fibronectin at both mRNA and protein levels in all three cell lines ( Figure 1, A and B).…”
Section: Jak2-stat5a/b Signaling Induces Expression Of Emt Markers Inmentioning
confidence: 99%
See 1 more Smart Citation
“…40,45,57,72,78,79 Active Stat5a/b decreased both cell surface and total E-cadherin protein expression ( Figure 1A) and mRNA levels ( Figure 1B). At the same time, active Stat5a/b upregulated mesenchymal markers N-cadherin, vimentin, and fibronectin at both mRNA and protein levels in all three cell lines ( Figure 1, A and B).…”
Section: Jak2-stat5a/b Signaling Induces Expression Of Emt Markers Inmentioning
confidence: 99%
“…50,51 Stat5a/b is activated by phosphorylation of a conserved C-terminal residue by an upstream kinase, most commonly Jak2, 52e54 which leads to Stat5a/b dimerization, nuclear translocation, DNA binding, and regulation of gene transcription. 55,56 Known key factors activating Stat5a/b in PC include prolactin (Prl), 40,45,57 growth hormone, 58 erythropoietin, 59 and epidermal growth factor. 60 In clinical PC, the expression of active Stat5a/b is elevated in >60% of PC metastases.…”
mentioning
confidence: 99%
“…PL also stimulates epithelial prostatic proliferation in vitro (Nevalainen et al, 1991). Further, the local, hormone-dependent production of PL in rat prostate was demonstrated (Nevalainen et al, 1991), together with the presence of PL receptors in the epithelium from normal (Nevalainen et al, 1997;Harris et al, 2004) and pathological prostate (Leav et al, 1999).…”
mentioning
confidence: 90%
“…In vitro, prolactin induces proliferation and antagonises apoptosis in prostate organ culture 1 and in some tumour cell lines 2,3 but not in others. 3,4 In vivo studies have consistently shown that hyperprolactinaemia induces prostate proliferation [5][6][7] and differentiation 8 in the rat prostate, and prolactin stimulated growth of the Dunning R3327 PAP tumour.…”
mentioning
confidence: 98%